Influence of UI, UX and E-Service Quality on Tokopedia Purchase Via Perceived Risk - Asta Kinan Prayoga; Gusti Noorlitaria Achmad; Zarina Zulkifli (International Journal Labs, 2023)
The development of technology and information have led to increase shopping activity on many e-commerce, especially in Indonesia. Tokopedia, one of the largest e-commerce in Indonesia, experienced a surge in transactions with high purchasing decisions. A high purchase decision indicates that the product or service has succeeded in attracting the attention of consumers and is related to engagement in choosing and making decisions to buy goods or use services. UI Design, UX Design and e-ServQual are the first aspects consumers feel when opening an application before making a purchase. Therefore, this research was conducted to determine the relationship between UI, UX, e-ServQual, Perceived Risk and Purchase Decision which are used as latent variables of this research. This study adopted a correlational research design and analysis was carried out using PLS-SEM method with SmartPLS 4.0 software. There are 114 respondents with various backgrounds and ages from all over Indonesia who use the Tokopedia mobile application. The results revealed that the factor that most influenced the purchasing decisions was e-ServQual with the indicator